Accuracy of the PARIS score and PCI complexity to predict ischemic events in patients treated with very thin stents in unprotected left main or coronary bifurcations. Issue 2 (21st May 2020) - Gallone, Guglielmo; D'Ascenzo, Fabrizio; Conrotto, Federico; Costa, Francesco; Capodanno, Davide; Muscoli, Saverio; Chieffo, Alaide; Yoichi, Imori; Pennacchi, Mauro; Quadri, Giorgio; Nuñez‐Gil, Ivan; Bocchino, Pier Paolo; et al.
Abstract: Background: The PARIS risk score (PARIS‐rs) and percutaneous coronary intervention complexity (PCI‐c) predict clinical and procedural residual ischemic risk following PCI. Their accuracy in patients undergoing unprotected left main (ULM) or bifurcation PCI has not been assessed. Methods: The predictive performances of the PARIS‐rs (categorized as low, intermediate, and high) and PCI‐c (according to guideline‐endorsed criteria) were evaluated in 3, 002 patients undergoing ULM/bifurcation PCI with very thin strut stents. Results: After 16 (12–22) months, increasing PARIS‐rs (8.8% vs. 14.1% vs. 27.4%, p  < .001) and PCI‐c (15.2% vs. 11%, p = .025) were associated with higher rates of major adverse cardiac events ([MACE], a composite of death, myocardial infarction [MI], and target vessel revascularization), driven by MI/death for PARIS‐rs and target lesion revascularization/stent thrombosis for PCI‐c (area under the curves for MACE: PARIS‐rs 0.60 vs. PCI‐c 0.52, p ‐for‐difference < .001). PCI‐c accuracy for MACE was higher in low‐clinical‐risk patients; while PARIS‐rs was more accurate in low‐procedural‐risk patients. ≥12‐month dual antiplatelet therapy (DAPT) was associated with a lower MACE rate in high PARIS‐rs patients, (adjusted‐hazard ratio 0.42 [95% CI: 0.22–0.83], p = .012), with no benefit in low to intermediate PARIS‐rs patients. No incremental benefit with longer DAPT was observed in complex PCI. Conclusions: In the setting of ULM/bifurcation PCI, the residual ischemic risk is better predicted by a clinical risk estimator than by PCI complexity, which rather appears to reflect stent/procedure‐related events. Careful procedural risk estimation is warranted in patients at low clinical risk, where PCI complexity may substantially contribute to the overall residual ischemic risk.